Solid Waste Management System in Enugu Metropolis, South-Eastern Municipality, Nigeria - Onyishi, Chinedu J; Wali, Elekwachi; Okwakpam, Ikechi O (Journal of Geography, Environment and Earth Science International, 2023)
Waste management and characterization is a fundamental step for effective and sustainable waste management strategies in order to safeguard environmental health. This study investigated the working system of Municipal solid waste management system (MSWMS) in all the zones of Enugu metropolis both by residents and by the municipal authority- Enugu State Waste Management Authority ESWAMA). Enugu metropolis as a geographical entity has been zoned into: LGAs, zones, wards, layouts among others for a well structured questionnaire administration. Available records in the ESWAMA main office indicates that Enugu metropolis was divided into ten (10) zones based on their SWM coverage schedule. Findings revealed that the elements of MSWMS in the metropolis include: waste collection, transfer, separation, recycling, and disposal. Furthermore ,the study revealed no form of solid waste separation before being dumped for transfer and disposal. The only form of recycling in the study area however is the done by the scavengers and their activities include: separation and selling of valuables recovered from solid waste dumpsites. Conclusively this study reveals that 30.7% (7.0% daily+23.7% 2-3days) of households are served within (1-3days) collection of SWs from dumpsites in their areas whereas 58.0% (31.3% 4days-1week+26.0% above 1week) said that collection of SWs at dumpster or at approved dumpsites delayed for 4days to over a week. The study recommends building cognizance on the need to sort waste from source before disposal and also inspire embracing of recycle and reuse of wastes to reduce wastes generated.
Keywords: Solid waste management; waste generation; waste characterization; ESWAMA.